Ischemic Stroke After Emergency Department Discharge for Symptoms of Transient Neurological Attack. (July 2018) - Parikh, Neal S.; Merkler, Alexander E.; Kummer, Benjamin R.; Kamel, Hooman
Background and Purpose: The significance of transient neurological attack (TNA) symptoms is unclear. We sought to determine the risk of ischemic stroke after discharge from the emergency department (ED) with a diagnosis consistent with symptoms of TNA. Methods: Using administrative claims data, we identified patients discharged from EDs in New York between 2006 and 2012 with a primary discharge diagnosis of a TNA symptom, defined as altered mental status, generalized weakness, and sensory changes. The primary outcome was ischemic stroke. We used Kaplan-Meier survival statistics to calculate cumulative rates, and Cox regression to compare stroke risk after TNA versus after transient ischemic attack (TIA; positive control) or renal colic (negative control) while adjusting for demographics and vascular risk factors. Results: Of 499 369 patients diagnosed with a TNA symptom and discharged from the ED, 7756 were hospitalized for ischemic stroke over a period of 4.7 (±1.9) years. At 90 days, the cumulative stroke rate was 0.29% (95% confidence interval [CI]: 0.28%-0.31%) after TNA symptoms versus 2.08% (95% CI: 1.89%-2.28%) after TIA and 0.03% (95% CI: 0.02%-0.04%) after renal colic. The hazard ratio (HR) of stroke was higher after TNA than after renal colic (HR: 2.13; 95% CI: 1.90-2.40) but significantly lower than after TIA (HR: 0.47; 95% CI: 0.44-0.50). Compared to TIA, TNA was less strongly associated with stroke among patients under 60 years of age compared to those over 60. Conclusions: Patients discharged from the ED with TNA symptoms faced a higher risk of ischemic stroke than patients with renal colic, but the magnitude of stroke risk was low, particularly compared to TIA.